Human Resource Innovation for Economic Inclusion: A Dual-Method Review on Global Trends and Gaps - Ratnawati, Shinta; Sari, Dewi Purnama; Atmaja, Hanung Eka; Anggraeni, Dewi; Khoirunnisa, Alya Najla (Entrepreneurship and Small Business Research, 2024)
Human resource (HR) innovation has emerged as a critical lever for advancing economic inclusion in increasingly digital and unequal labor markets. However, existing scholarship remains conceptually fragmented and weakly integrated across theoretical and contextual domains. This study provides a comprehensive synthesis of global research on HR innovation for economic inclusion by employing a dual-method approach that combines bibliometric analysis and a systematic literature review (SLR). A dual-method review was employed, combining bibliometric analysis and a systematic literature review (SLR). The dataset consists of 220 peer-reviewed articles indexed in Scopus and published between 2020 and 2024. Bibliometric techniques were used to map publication trends, influential authors, institutions, and journals, while the SLR identified thematic patterns and conceptual linkages. The analysis reveals four dominant research clusters: (1) inclusive skills development and workforce upskilling, (2) diversity-oriented HR strategies, (3) digital inclusion in HR systems, and (4) HR contributions to social resilience among vulnerable communities. Despite growing scholarly attention, the literature remains fragmented and weakly connected to macro-level equity and inclusion strategies. The study provides a consolidated knowledge base and proposes a future research agenda to strengthen theoretical integration and policy relevance in inclusive HR innovation. This research offers an integrative global synthesis of HR innovation for economic inclusion by combining bibliometric mapping and SLR, highlighting underexplored theoretical and practical gaps in the field.